Approaches to control mechanisms and their implications for companies’ profitability: a study in UAE - Muhammad Shabir, Shaharudin; Ahmed, Essia Ries; Alabdullah, Tariq Tawfeeq Yousif (Universitas Muhammadiyah Sidoarjo, 2020)
This study tries to evaluate and test the role of control mechanisms represented by foreign ownership and insider ownership on companies’ profitability in the listed companies in the UAE and whether independent variables are matter in determining the profitability of such companies. This study utilized companies belong to non-financial sector for the year of 2019 with a sample of 50 companies to be analyzed in the current study. To test the independent and dependent variables, regression analysis was used via using SPSS. The findings show that insider ownership has insignificant impact on companies’ profitability On the other hand, the findings revealed evidence to support the effect of foreign ownership on companies’ profitability. Moreover, there is insignificant evidence reflected the fact that companies’ size has insignificant impact on companies’ profitability. This study added further evidence in Dubai context where there is a rare and unique studies that have been done in this important context. It takes in tits account to investigate both insider and foreign ownership and their impact companies’ profitability